THE CORRELATION BETWEEN THE FREQUENCY OF SMOKING AND THE INTENTION TO QUIT AMONG HEALTH PROVIDERS AND TEACHERS IN BANTUL DISTRICT, YOGYAKARTA - , MIA KANTIASIH RAJASA, Dra. Retna Siwi Padmawati, MA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : Smoking may be on a decreasing trend in many parts of the world, but in Indonesia this health hazard has been on an increase where the WHO has stated that an approximate 61 million (36.1%) Indonesian are smokers. Health providers and teachers have an upstanding in the community as role models and health promoters and yet some of them still practice the habit of smoking. It is general knowledge that frequency of smoking directly relates to its health hazards, but its association to an individuals intention to quit smoking altogether is still arguable â especially for those in pulation. a specific po Objective : To understand the correlation between the frequency of smoking and the intention to quit among health providers and teachers in the District of Bantul, Yogyakarta. Method : Cross sectional study by self administered survey questionnaires with a total of 149 teachers and 80 PHC personnel in Bantul District. Pearson Chi square was used for data analysis. Result : In both health providers and teachers, there were more light smokers than heavy smokers, in which the amount of heavy smokers who had intention to quit in teachers were 72% and 78% within 24 hours and 7 days respectively, and among health providers 70.6% and 62.5%.These results did not portray much difference ght smokers who had intention to quit. than those light smokers who had intention to quit.